Auditory Long Latency Responses in Children with Learning Disabilities - Puneet Sharma (Light House Polyclinic Mangalore, 2021)
Objective of the study : To measure and compare the latencies of P1, N1 & P2 of ALLR in children with learning disability. Methodology: For 20 children diagnosed with learning disability (LD), Pure Tone Audiometry, Speech Audiometry, Impedance Audiometry, and ALLR were obtained, and the results were compared to a control group. Important Findings: Between children with LD and the normal control group, there were highly statistically significant variations in the amplitudes of the waves P1, N1, and P2. The latencies of the ALLR waves P1, N1, P2, and N2 did show differences, though the results did not reach statistical significance. These results indicate that children with LD may have problems in auditory sensory processing. Conclusions: Auditory Long Latency Responses can be used for the early detection of children with learning disabilities and provides the opportunity to plan the treatment for improvement of auditory skills.